Von Willebrand Factor Aggravates Hepatic Ischemia–Reperfusion Injury by Promoting Neutrophil Recruitment in Mice - Urisono, Yasuyuki; Sakata, Asuka; Matsui, Hideto; Kasuda, Shogo; Ono, Shiro; Yoshimoto, Kiyomi; Nishio, Kenji; Sho, Masayuki; Akiyama, Masashi; Miyata, Toshiyuki; Okuchi, Kazuo; Nishimura, Satoshi; Sugimoto, Mitsuhiko (Thrombosis and Haemostasis, 2018)
Hepatic ischaemia–reperfusion (I/R) injury is a serious liver damage that critically influences the clinical outcome of liver surgery or transplantation. Since recent studies indicated the critical involvement of von Willebrand factor (VWF) in reperfusion injuries of brain and myocardium, we hypothesized that VWF-dependent thrombotic or inflammatory responses also play a role in hepatic I/R injury. Using a mouse model of hepatic I/R injury, we explored the functional relevance of the VWF–ADAMTS13 (a disintegrin and metalloproteinase with a thrombospondin type 1 motif, member 13) axis in this pathologic condition. Time-course studies during hepatic I/R revealed significantly lower alanine aminotransferase (ALT) values, as well as greater hepatic blood flow, in VWF gene-deleted (KO) mice in comparison with wild-type (WT) mice. Histological analysis revealed a significantly lesser extent of neutrophil infiltration and hepatocellular necrosis in liver tissues of VWF-KO mice. Human recombinant ADAMTS13 significantly improved the impairment in ALT values and hepatic blood flow and decreased neutrophil infiltration within the liver tissue of WT mice. Real-time intravital imaging successfully visualized significantly reduced leukocyte–vessel wall interactions in I/R liver of VWF-KO mice. Taken together, our results indicate that VWF promotes neutrophil recruitment in ischaemic mouse liver, critically aggravating reperfusion injury, and suggest that functional regulation of VWF by ADAMTS13 represents a promising therapeutic option for hepatic I/R injury.
Keywords: von Willebrand factor; ADAMTS13; hepatic ischaemia–reperfusion injury; neutrophil recruitment